PENGARUH GAYA HIDUP MODE, BAURAN PROMOSI DAN PRESENTASI PRODUK TERHADAP KEPUTUSAN PEMBELIAN RECYCLE STUFF.ID KOTA SAMARINDA - Hardi Mardani M (Jurnal Manajemen Bisnis Krisnadwipayana, 2022)
This study aims to analyze and find out “effect of fashion lifestyle, promotion mix and visual merchandising on purchase decisions in Recycle Stuff.id Samarinda City. This research uses quantitative research and sampling using non probability sampling technique, the data is obtained from distributing questionnaires through google from. The results of this study indicate that the variables of fashion lifestyle, promotion mix and visual merchandising simultaneously have a significant effect on purchasing decisions.